Physiological and transcriptional responses to heat stress and functional analyses of PsHSPs in tree peony (Paeonia suffruticosa) - Ma, Jin; Wang, Jie; Wang, Qun; Shang, Linxue; Zhao, Yu; Zhang, Guozhe; Ma, Qingqing; Hong, Sidan; Gu, Cuihua (Frontiers in Plant Science, 2022)
Tree peony (Paeonia suffruticosa) is a traditional Chinese flower that is not resistant to high temperatures, and the frequent sunburn during summer limits its normal growth. The lack of understanding of the molecular mechanisms in tree peony has greatly restricted the improvement of novel heat-tolerant varieties. Therefore, we treated tree peony cultivar ‘Yuhong’ (P. suffruticosa ‘Yuhong’) at normal (25°C) and high temperatures (40°C) and sequenced the transcriptomes, to investigate the molecular responsive mechanisms to heat stress. By comparing the transcriptomes, a total of 7673 differentially expressed genes (DEGs) were detected comprising 4220 upregulated and 3453 downregulated genes. Functional annotation showed that the DEGs were mainly related to the metabolic process, cells and binding, carbon metabolism, and endoplasmic reticulum protein processing. qRT-PCR revealed that three sHSP genes (PsHSP17.8, PsHSP21, and PsHSP27.4) were upregulated in the response of tree peony to heat stress. Tissue quantification of the transgenic lines (Arabidopsis thaliana) showed that all three genes were most highly expressed in the leaves. The survival rates of transgenic lines (PsHSP17.8, PsHSP21, and PsHSP27.4) restored to normal growth after high-temperature treatment were 43, 36, and 31%, respectively. In addition, the activity of superoxide dismutase, accumulation of free proline, and chlorophyll level were higher than those of the wild-type lines, while the malondialdehyde content and conductivity were lower, and the membrane lipid peroxidation reaction of the wild-type plant was more intense. Our research found several processes and pathways related to heat resistance in tree peony including metabolic process, single-organism process, phenylpropane biosynthesis pathway, and endoplasmic reticulum protein synthesis pathway. PsHSP17.8, PsHSP21, and PsHSP27.4 improved heat tolerance by increasing SOD activity and proline content. These findings can provide genetic resources for understanding the heat-resistance response of tree peony and benefit future germplasm innovation.